General movements in genetic disorders: A first look into Cornelia de Lange syndrome. (August 2015) - Marschik, Peter B.; Soloveichick, Marina; Windpassinger, Christian; Einspieler, Christa
Abstract The assessment of General Movements (GMs), i.e. age-specific motor patterns during the first months of life, has repeatedly proven to be a valuable tool to predict neurodevelopmental outcomes. Abnormal spontaneous GMs were found to be among the most reliable markers for cerebral palsy. To add to the knowledge of the abnormal early motor repertoire we analysed prospectively collected video recordings of a boy clinically diagnosed with Cornelia de Lange syndrome. The observed atypical GMs are a further step to disentangle early motor peculiarities in the light of the genetic impact on the developing brain.